Applying the Relative Acculturation Extended Model to Examine Black Americans' Perspectives on African Immigrant Acculturation. (October 2017) - Thelamour, Barbara
This study used the Relative Acculturation Extended Model to capture Black Americans' ( N = 173) perceptions of and preferences for African immigrant acculturation to the Black American host culture in seven life domains (i.e., social relationships, values, spending, family dynamic, group educational concern, race relations, and political engagement). Participants also had the opportunity to provide qualitative statements to elaborate on their survey responses. Contrary to existing literature, survey analyses showed that Black Americans generally perceived African immigrants as integrated. More than half of the domains were found to be under the separation acculturation strategy. In addition, integration was the strategy most preferred. Marginalization was not an acculturation strategy that Black Americans observed or wanted. Within-subject ANOVAs revealed main effects of domain, perceptions (vs. preferences), but not for culture. Analysis of the qualitative statements expanded the quantitative findings, not only highlighting the places Black Americans perceive difference, but also emphasizing their hope for African immigrant acculturation to and alliance with their culture. The emphasis on Black Americans as the host culture provides an alternative but much-needed view on immigrant acculturation, adding nuance to the long-standing narrative of contention between these two groups.